(untitled) (Khwopa Journal, 2023)
This study’s goal is to evaluate the causal relation among Nepal’s exports, imports, and real gross domestic product. One of the most significant sources of foreign currency income that reduces the strain on the balance of payments is considered to be exports. The relationship between real GDP, exports and imports is investigated on Nepalese economy over the period 1975-2020, using yearly data. For that purpose, Vector Autoregressive model is used as there is no cointegration among variables as per Johansen’s approach. Similarly variance decomposition test is also conducted. Findings confirm the presence of relationship among Real GDP, exports and imports. The results of VAR granger causality test shows that surprisingly export doesn’t cause real GDP and import whereas import causes real GDP. Similarly, real GDP causes export, and import also causes export. But there is no bi-directional causality between the variables. Nepal will gain from raising its international trade competitiveness to reduce current account deficits. Prioritizing research and development and producing export goods with high value added by focusing on science and technology are the simplest ways to do this. Similarly, in order to raise worker productivity, which will immediately spur economic growth and raise living standards in Nepal, there is a need to increase technology imports.